Capsaicin`s role in mitigating muscle soreness and enhancing futsal players` recovery after exercise-induced muscle damage - Rashki, M.; Hemmatinafar, M.; Safari, K.; Imanian, B.; Rezaei, R.; Koushkie Jahromi, M.; Suzuki, K. (Nutrients, 2025)
Background: Capsaicin, known for its antioxidant and antibacterial properties, may mitigate oxidative stress and inflammation associated with exercise-induced muscle damage (EIMD). This study evaluates the efficacy of capsaicin supplementation in reducing delayed-onset muscle soreness (DOMS) and enhancing strength and power in collegiate male futsal players.